HUBUNGAN ANTARA FAKTOR INDIVIDU DAN FAKTOR PEKERJAAN TERHADAP STRES KERJA PADA PEKERJA BAGIAN PRODUKSI DI PTX - Daffa Ade Azmi (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Work stress is an emotional state that arises due to the mismatch of the workload with the individual's ability to deal with the pressure of the pressure they face. The purpose of this study was to analyze individual factors and work factors related to work stress in production employees in the area of PT X. This research method is an analytical descriptive research with cross sectional approach. The population in this study amounted to 42 workers and sampling techniques using total sampling in which the number of samples equal to the number of population. The measurement of work stress is measured by referring to the regulation of the Minister of manpower No. 5 of 2018. Of the 42 people who responded, as many as 35 workers experienced stress with medium category and the remaining 7 workers experienced stress with low category. The results of statistical tests using spearmans rank showed that there was no relationship between individual factors and occupational factors. Individual factors that include age have a relationship that is unidirectional while factors of education and marital status have a relationship that is not unidirectional. As for the employment factors include length of service, work shifts and physical workload have a unidirectional relationship and for the distance of residence has a non-directional relationship. Then it is advisable for the company to provide promotion opportunities for promotion to all production employees fairly, such as appointing permanent employees. The existence of a fair promotion makes employees can be excited when working so that the level of work stress becomes low Keywords: Work stress, individual factors, occupational factors